Isolated Pauci-Immune Pulmonary Capillaritis Associated with Hydrocarbon Inhalation and Marijuana Smoking: An Unusual Case of Severe Hypoxemia - Jason S. Oh; Uni Wong; Divyansh Bajaj; Stella E. Hines (Case Reports in Pulmonology)
We present a case report of a patient with Isolated pauci-immune pulmonary capillaritis (IPIPC). A 40-year-old male presented with acute onset severe hypoxemic respiratory failure. He had just returned home from work as a cabinetmaker, where he experienced inhalational exposure to hydrocarbons and solvents, and had smoked a marijuana cigarette. He was hypotensive, and his chest imaging showed bilateral dependent infiltrates. His hypoxemia made little improvement after conventional ventilator support and broad-spectrum antibacterial therapy and he was considered too unstable to tolerate diagnostic bronchoscopy with bronchoalveolar lavage. His laboratory evaluation initially showed microscopic hematuria which later cleared, but other tests including serologic autoimmune assessment were negative, and he did not have any traditional risk factors for vasculitis. A video-assisted thoracoscopic lung biopsy revealed diffuse alveolar hemorrhage with pulmonary capillaritis on histopathology. He was diagnosed with IPIPC and initiated on immunosuppressive therapy. He was soon liberated from mechanical ventilation and improved to hospital discharge. Diffuse alveolar hemorrhage from Goodpasture’s Syndrome has manifested following inhalation of hydrocarbons and following smoking. This has not previously been reported with IPIPC. Given the lack of other findings and risk factors, his IPIPC was likely associated with occupational exposures to hydrocarbons as a cabinetmaker compounded by marijuana smoking.